ANALISA SUPPLY CHAIN RISK MANAGEMENT BERDASARKAN METODE FAILURE MODE AND EFFECTS ANALYSIS (FMEA) - Nurlailah Badariah; Dadang Surjasa; Yuda Trinugraha (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2012)
Today PT. Jakarta Pertamina Unit Produksi Pelumas Jakarta (UPPJ) has some problems with inbound supply of raw materials. Deficiency dock may pose risks to the process of loading raw material base oil, resulting in delay in supply of raw materials. This delay could have an impact on other processes, such as delays to produce, and iddle of existing production facilities at the plant; it would be very detrimental to the company if the obstacle is often the case. Supply chain management is always influenced by three factors, namely how to reduce costs, reduce time and improve quality. If at first study on supply chain management is only classified in three categories, namely the field of operations, design and strategy, then this can be added to the four categories, namely the field of risk, which is commonly referred to as supply chain risk Management (SCRM). Based on the problems that occurred the first stage done is to identify risks in each process and then determine the influence of the effect in terms of cost, time and quality of the results of the determination of the influence. the next step is to determine the weights based on the severity of the bottleneck (severity), the possibility of resistance (Occurrence) and the possible causes of the barriers can be detected (Detection). The last step is to calculate the Risk priority Number (RPN) is obtained from the product of severity, Occurrence and Detection then obtained the highest priority for 144 the factors that most influence the leak rate of the production process.